Chitinase1 contributed to a potential protection via microglia polarization and Aβ oligomer reduction in D-galactose and aluminum-induced rat model with cognitive impairments. (4th July 2017) - Xiao, Qian; Yu, Weihua; Tian, Qi; Fu, Xue; Wang, Xia; Gu, Min; Lü, Yang
Highlights: Chitinase1 activity was both improved in D-galactose/AlCl3 -treated rats and Aβ-oligomer-pretreated microglia. There was an improvement of cognitive function in chtinase1-treated AD rats. Chitnase1 could weaken the deposition of Aβ oligomers in brain of AD rats. Chtinase1 polarized microglia into anti-AD M2 phenotype in cultured N9 microglia cells. Abstract: Chitinase activity is increased in Alzheimer's disease (AD). However, the role of chitinase1 in AD is unknown. We investigated the effects of chitinase1 on Alzheimer's pathology and microglia function. Artificial chitinase1 and chitinase inhibitor (chitinase-IN-2) were used to determine the effects of chitinase1 on inflammatory factors and β-amyloid (Aβ) oligomers deposition in D-galactose/AlCl3 -induced rat model with cognitive impairments. Aβ-treated N9 microglia cells were analyzed to further verify whether the changes in inflammatory factors following chitinase1 treatment were associated with microglia alternative activation. Our data displayed that the activity of chitinase1 was both improved in D-galactose/AlCl3 -injected rats and Aβ-pretreated microglia. Moreover, there was an improvement in cognitive function in chitinase1-treated AD rats. Furthermore, anti-inflammation factors (Arginase 1, Arg-1, mannose receptor type C 1, MRC1/CD206) were increased and pro-inflammation factors (tumor necrosis factor alpha, TNFα, interleukin 1 beta, IL-1β) were decreased in D-galactose/AlCl3 -induced AD rats with chitinase1 treatment. A higher level of M2 markers (Arg-1, MRC1/CD206) and a lower level of classic M1 markers (TNFa, IL-1β) were obtained in Aβ-pretreated N9 cells with chitinase1, suggesting that chitinase1 polarized the microglia into an anti-AD M2 phenotype. We also detected that chitnase1 could weaken the deposition of Aβ oligomers in the brain of D-galactose/ AlCl3 - induced AD rats. In conclusion, Chitinase1 might exert protective effects against AD by polarizing microglia to an M2 phenotype and resisting Aβ oligomer deposition.